The need for a new approach in cholesterol management - Hobbs, R (2004)
By the year 2020, cardiovascular disease will be the world's biggest cause of premature death. As the plasma cholesterol is lowered, the incidence of coronary heart disease (CHD) events is reduced. European data on secondary prevention show that many patients have not had a plasma cholesterol recorded - even those with a diagnosis of CHD. English data show that only half of patients with a cholesterol measurement are being prescribed a statin, and only half of those are being treated to target. Poor public understanding of this subject area is one obstacle to progress.